Heavy precipitation in a changing climate: Does short‐term summer precipitation increase faster?. Issue 4 (18th February 2015) - Ban, Nikolina; Schmidli, Juerg; Schär, Christoph
Abstract Climate models project that heavy precipitation events intensify with climate change. It is generally accepted that extreme day‐long events will increase at a rate of about 6–7% per degree warming, consistent with the Clausius‐Clapeyron relation. However, recent studies suggest that subdaily (e.g., hourly) precipitation extremes may increase at about twice this rate. Conventional climate models are not suited to assess such events, due to the limited spatial resolution and the need to parametrize convective precipitation (i.e., thunderstorms and rain showers). Here we employ a convection‐resolving model using a horizontal grid spacing of 2.2 km across an extended region covering the Alps and its larger‐scale surrounding from northern Italy to northern Germany. Consistent with previous results, projections using a Representative Concentration Pathways version 8.5 greenhouse gas scenario reveal a significant decrease of mean summer precipitation. However, unlike previous studies, we find that both extreme day‐long and hour‐long precipitation events asymptotically intensify with the Clausius‐Clapeyron relation. Differences to previous studies might be due to the model or region considered, but we also show that it is inconsistent to extrapolate from present‐day precipitation scaling into the future.